Networks of research collaboration within World Education Research Association (The Journal of Psychology and Sociology, 2021)
The paper focuses on the issue of advancing education research through research networking, and it directs our attention to one of the World Education Research Association program, which is called World Education Research Association-International Research Networks, WERA-IRNs. The program pro- motes and supports the development of high quality research, particularly with regard to creating the conditions for high-quality research through research networking in education. Reflecting on the aims of WERA-IRNs and its more than 10-year history (2010-2021), and what is already part of the WERA practice in sustaining and developing the WERA-IRNs program, it is visible that WERA-IRNs can serve as an important model for advancing education research through international research collaboration. For the purposes of the paper a historical analysis of source materials is used. The paper concludes with thoughts on future research on networks of research collaboration and science policy challenges in the era of collaborative turn in science. Research on scientific collaboration networks should be connected with the smart approach towards scientific collaboration policy and its challenges. It is necessary to take into account the horizontal nature of scientific collaboration policies, and the variety of levels at which science policies can be designed and implemented.Key words: geography of science, research network, scientific collaborative turn in science, scien-tific associations, research capacity building, World Education Research Association (WERA), World Education Research Association International Research Networks (WERA-IRNs).